PERGESERAN NILAI DALAM KEHIDUPAN SOSIAL BUDAYA DAN PENDIDIKAN DI LINGKUNGAN SEKOLAH DASAR (PERSPEKTIF AGAMA DAN KULTURAL) - Mali, Muhamad Masyhuri; Nasir Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article was created aiming to find out how important it is to maintain the nation’s character in the pressure of the transitional era which is the main factor in the occurrence of a shift in the value of life which includes social, cultural, and educational views from the perspective of religion and culture. Descriptive qualitative by upholding a rational mind, with the stages that have been arranged as a whole to become a unity which later this article is expected to be a lesson for readers and writers, by focusing on how the factors that influence the occurrence of shifts in values in social life culture and education, and explore what factors make society unable to survive in the swift currents of globalization and the times.